Peran Pendidikan Kewirausahaan dalam Meningkatkan Kreativitas dan Inovasi Berwirausaha Mahasiswa Wirausaha Merdeka STKIP PGRI Lumajang - Triwilujeng Ayuningtyas; Novi Rahmawati (Jurnal Pendidikan Ekonomi Undiksha, 2026)
This research is based on the lack of creativity and entrepreneurial innovation among students. This condition indicates that the theoretical knowledge acquired has not yet been fully applied into practical skills, mainly due to limitations in capital and resources, as well as challenges related to market acceptance of innovative products. This research aims to analyze the role of entrepreneurship education in enhancing students' creativity in generating new business ideas and applying them innovatively. This research provides empirical evidence regarding the success of entrepreneurship learning based on the Independent Entrepreneurship Program in shaping young entrepreneurs who are adaptive and innovative. This research uses a qualitative research method with a narrative approach. Data collection techniques include observation, documentation, and in-depth interviews with 12 student participants of the Independent Entrepreneurship Program, class 2 of 2023. Data analysis is conducted through the stages of data reduction, data presentation, and drawing conclusions. Research results show that entrepreneurship education in the Independent Entrepreneurship Program plays a role in enhancing students' entrepreneurial creativity and innovation, such as generating unique business ideas, creatively utilizing resources, and developing innovative marketing strategies. Student innovation also increases through the introduction of technology, team collaboration, and mentor guidance.